2016
DOI: 10.1002/eji.201646656
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomic analysis of type 1 diabetes associated HLA‐DQ molecules and the impact of HLA‐DM on peptide repertoire editing

Abstract: HLA-DM and class II associated invariant chain (Ii) are key cofactors in the MHC class II (MHCII) antigen processing pathway. We used tandem mass spectrometry sequencing to directly interrogate the global impact of DM and Ii on the repertoire of MHCII-bound peptides in human embryonic kidney 293T cells expressing HLA-DQ molecules in the absence or presence of these cofactors. We found that Ii and DM have a major impact on the repertoire of peptides presented by DQ1 and DQ6, with the caveat that this technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…In a study of DR3-expressing T2 cells transfected with different levels of DM, Alvaro-Benito et al found that higher DM expression was associated with presentation of MHC-II-bound peptides with lower predicted MHC-II binding affinity (51). In a study comparing the peptide repertoires of 293T cells transfected with HLA-DQ molecules differentially associated with type 1 diabetes, Zhou et al found that in the absence of DM, peptides with lower binding affinity and faster dissociation were presented (76). These studies agree with our data with respect to DM-sensitive epitopes, in which peptides eluted only in the presence of DO were determined to be more sensitive to DM-mediated exchange.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of DR3-expressing T2 cells transfected with different levels of DM, Alvaro-Benito et al found that higher DM expression was associated with presentation of MHC-II-bound peptides with lower predicted MHC-II binding affinity (51). In a study comparing the peptide repertoires of 293T cells transfected with HLA-DQ molecules differentially associated with type 1 diabetes, Zhou et al found that in the absence of DM, peptides with lower binding affinity and faster dissociation were presented (76). These studies agree with our data with respect to DM-sensitive epitopes, in which peptides eluted only in the presence of DO were determined to be more sensitive to DM-mediated exchange.…”
Section: Discussionmentioning
confidence: 99%
“…HLA/peptide complex and TCR binding determines the specificity of immune response [44], [45], [46]. HLA genotyping in 6 T1D patients (Table S1) indicated that alleles such as A*24:02 , B*58:01:01 , C*03:02 , DRB1*03:01 , DRB1*09:01:02 , DQB1*03:02:01 , and DQB1*02:01:01 are frequently expressed in these patients, suggesting that these types of HLAs may play roles in T1D biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Within the pathway, the human leukocyte antigen-DM (HLA-DM) protein enhances peptide loading of MHCII complexes by differentially catalyzing peptide exchange reactions on classical MHCII molecules (3)(4)(5)(6)(7)(8)(9)(10). Through this action, HLA-DM markedly impacts the specificity of antigen presentation by continuously proofreading the peptide-MHCII complexes that are en route for presentation to CD4 ϩ T cells (8,9,(11)(12)(13).…”
mentioning
confidence: 99%